Modelling of Laboratory Information Systems in Higher Education Based on Enterprise Architecture Planning for Optimizing Monitoring and Equipment Maintenance - Ifriza, Yahya Nur; Veronika, Trisni Wulandari; Suryarini, Trisni; Supriyadi, Antonius (IJIE (Indonesian Journal of Informatics Education), 2022)
Retracted on author's request